Menuju Gereja Integratif Berbasis Ibadah Intergenerasi: Perwujudan Komunitas Rekonsiliatif Sebagai Epifani Gereja - Budianto Lim (Veritas : Jurnal Teologi dan Pelayanan, 2022)
This article presents reasons for manifesting the church as a community of reconciliation as her core identity through an intergenerational worship setting that integrates the whole body of Christ. This research is vital because churches generally show internal disintegration through weekly fragmentation in worship. Separation of generations who are supposedly one big family of God continues to happen based on social and psychological reasons to the extent of forgetting the universal sinfulness of humanity and their basic needs. The author elaborates on two fundamental reasons through biblical-theological methods. He analyses the liturgical ecclesiology of Jean-Jacques von Allmen in the context of war and the post-war era, which influences his theological formulation about the substance of reconciliation as the epiphany of the church. Such conviction is substantiated by another biblical analysis concerning four terminologies used in Revelation (tribe, people, language, and nation) and literary analysis of 2 Corinthians that set reconciliation as its center. Both theological and biblical analyses provide a strong foundation for churches to integrate all of God’s people as a reconciliatory community in the world. The author views the discussion of theological and biblical basis have not being tied to the worship life of a church that needs to embrace all people through intergenerational worship. This notion would be a contribution to the Christian community in Indonesia.